Disabling Vertigo and Tinnitus Caused by Intrameatal Compression of the Anterior Inferior Cerebellar Artery on the Vestibulocochlear Nerve: A Case Report, Surgical Considerations, and Review of the Literature - Borghei-Razavi, Hamid; Darvish, Omid; Schick, Uta (Journal of Neurological Surgery Reports, 2014)
Microvascular compression of the vestibulocochlear nerve is known as a cause of tinnitus and vertigo in the literature, but our review of the literature shows that the compression is usually located in the cerebellopontine angle and not intrameatal.We present a case of intrameatal compression of the anterior inferior cerebellar artery (AICA) on the vestibulocochlear nerve of a 40-year-old woman with symptoms of disabling vertigo and intermittent high-frequency tinnitus on the left side without any hearing loss for ∼ 4 years. Magnetic resonance imaging of the brain did not show any abnormality, but magnetic resonance angiography showed a left intrameatal AICA loop as a possible cause of the disabling symptoms. After the exclusion of other possible reasons for disabling vertigo, surgery was indicated. The intraoperative findings proved the radiologic findings. The large AICA loop was found extending into the internal auditory canal and compressing the vestibulocochlear nerve. The AICA loop was mobilized and separated from the vestibulocochlear nerve.The patient's symptoms resolved immediately after surgery, and no symptoms were noted during 2 years of follow-up in our clinic. Her hearing was not affected by the surgery.In addition to other common reasons, such as acoustic neuroma, disabling vertigo and tinnitus can occur from an intrameatal arterial loop compression of the vestibulocochlear nerve and may be treated successfully by drilling the internal acoustic meatus and separating the arterial conflict from the vestibulocochlear nerve.
Keywords: anterior inferior cerebellar artery; microvascular decompression; vertigo; internal auditory canal